THE ADDITION OF SURIMI INDIAN MACKEREL (Rastrelliger kanagurta) TO THE SENSORY AND CHEMICAL CHARACTERISTICS OF MANTOU - Putri, Zaky Yoana; Pratama, Rusky Intan; Herman, Roffi Grandiosa; Rostini, Iis (Universitas Mataram, 2025)
This study aims to determine the most preferred percentage of indian mackerel surimi addition to mantou based on panelist evaluations. The research was conducted from December 2024 to March 2025 using an experimental method with four treatments (0%, 20%, 30%, and 40%) and 20 panelist as the retest. Panelist acceptance was assessed using a hedonic test and Bayes analysis. The hedonic test data were analyzed using the Friedman test. The most preferred mantou sample was further analyzed for its nutritional content through proximate analysis. The results showed no significant differences among treatments in terms of panelist preference. However, the control mantou (0%) and the mantou with 40% Indian mackerel surimi addition had the highest preference scores. The 40% treatment received the highest mean score for appearance (7.90), while the A (0%) control sample scored highest for aroma (8.10) and taste (8.00). Both treatments had the same texture score (7.80). The highest alternative value in the Bayes test was obtained by treatment D (40%) which amounted to 8.03. Proximate analysis revealed that the addition of mackerel surimi tended to increase the nutritional content of mantou, except for carbohydrates. The , 40% surimi mantou had 39.35% moisture, 1.13% ash, 5.17% fat, 10.49% protein, and 43.86% carbohydrates. Meanwhile, the control mantou contained 31.15% moisture, 0.98% ash, 4.57% fat, 8.28% protein, and 55.02% carbohydrates.